2022
DOI: 10.3389/fcimb.2022.839526
|View full text |Cite
|
Sign up to set email alerts
|

A Gut Feeling in Amyotrophic Lateral Sclerosis: Microbiome of Mice and Men

Abstract: Amyotrophic lateral sclerosis (ALS) is a severely debilitating disease characterized by progressive degeneration of motor neurons. ALS etiology and pathophysiology are not well understood. It could be the consequences of complex interactions among host factors, microbiome, and the environmental factors. Recent data suggest the novel roles of intestinal dysfunction and microbiota in ALS etiology and progression. Although microbiome may indeed play a critical role in ALS pathogenesis, studies implicating innate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 88 publications
(146 reference statements)
0
30
0
Order By: Relevance
“…One of these data found was that the intestinal microbiota can translocate to the bloodstream when intestinal vascular permeability is evident and metabolites triggered by bacteria can control glutamate and GABA, generating stress in the CNS. In this sense, the presence of LPS in blood circulation was detected in stressed rats [20][21][22].…”
Section: Composition Of the Microbiota Of Patients With Alsmentioning
confidence: 88%
See 1 more Smart Citation
“…One of these data found was that the intestinal microbiota can translocate to the bloodstream when intestinal vascular permeability is evident and metabolites triggered by bacteria can control glutamate and GABA, generating stress in the CNS. In this sense, the presence of LPS in blood circulation was detected in stressed rats [20][21][22].…”
Section: Composition Of the Microbiota Of Patients With Alsmentioning
confidence: 88%
“…The ENS and smooth muscle automatism are unable to modulate the motor functions of the digestive tract, which provides an anatomical explanation for these clinical manifestations. This process is related to the fact that 70-80% of the total number of human immune cells are within the lymph nodes of the intestinal mucosa, which suggests the possible role of the microbiota in the ability to impact neuroimmune [19][20][21]. Although the etiology of ALS is still not well established, the gut microbiota may mediate the pathology of the disease, mainly due to pro-inflammatory gut microbiomes (Figure 1).…”
Section: Relation Between Microbiota and Central Nervous Systemmentioning
confidence: 99%
“…This reflects, for example, a significant reduction of butyrate-producing bacteria in SOD 1 -mutant mice. Butyrate-producing bacteria are known to play important roles in the control of intestinal inflammatory processes, and the maturation of the immune system, because the short-chain fatty acid butyrate inactivates lymphocyte maturation [ 70 ].…”
Section: Pathogenic Risk Factors Involved In Alsmentioning
confidence: 99%
“…In addition, certain lactic acid bacteria, such as Lactobacillus plantarum and Lactobacillus amylovorus, are also likely to have anti-enteroviral activity [133,134]. Moreover, it has been shown that in ALS the disturbances in the balance of the intestinal microbiota are present [135].…”
Section: Anti-enteroviral Therapymentioning
confidence: 99%